Fuzzy Optimal Design of Gear Transmission Meschanism of Mooring Winch based on Matlab - Zhao Linlin; Huang Xiaoping; Li Jingzhong (Jixie chuandong)
Aiming at the optimal design of gear transmission of mooring winch with non- linear and multi- constraint and multi- factors,two- stage fuzzy optimization is put forward. Taking the mooring winch gear transmission mechanism of minimum volume as the design objective function and the design variables and performance constraints as the constraint conditions of fuzzy optimization,the fuzzy optimization design of gear transmission mechanism of mooring winch is carried out by using the optimization toolbox of Matlab. The result of optimization design show that,the more compact structure can be got,the material is saved and the weight of mooring winch is reduced.